2010
DOI: 10.1371/journal.pmed.1000277
|View full text |Cite
|
Sign up to set email alerts
|

Early Pandemic Influenza (2009 H1N1) in Ho Chi Minh City, Vietnam: A Clinical Virological and Epidemiological Analysis

Abstract: Rogier van Doorn and colleagues analyze the initial outbreak, attempts at containment, and establishment of community transmission of pandemic H1N1 influenza in Ho Chi Minh City, Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…The lack of significant differences in the persistence of PCR positivity in treated vs. untreated patients is in agreement with data from other studies carried out on seasonal influenza strains [27], and in apparent contrast with other studies, showing a significant shortening of the duration of viral shedding in A/H1N1pdm -patients exposed to NAI [28,10]. In another study conducted only in treated patients, more prolonged viral shedding was observed in subjects < 13 years of age than in older patients [15].…”
Section: Discussionsupporting
confidence: 92%
“…The lack of significant differences in the persistence of PCR positivity in treated vs. untreated patients is in agreement with data from other studies carried out on seasonal influenza strains [27], and in apparent contrast with other studies, showing a significant shortening of the duration of viral shedding in A/H1N1pdm -patients exposed to NAI [28,10]. In another study conducted only in treated patients, more prolonged viral shedding was observed in subjects < 13 years of age than in older patients [15].…”
Section: Discussionsupporting
confidence: 92%
“…There was little difference in the ranges of mean viral shedding duration between the adults (3–8 days) and children (4–8 days) with similar observations for the respective median values (Figure ). Comparison of viral shedding duration measured by PCR between community‐based child and adult cases was made directly in five studies; children had longer shedding duration in three of the studies, two by a mean of 1·2 days (of which P < 0·01 for one of the studies) and the other by 0·4 day but was longer in adults in the other studies by 0·4 and 1·0 days . An additional paper that compared shedding duration in community‐based cases but measured by viral culture found a mean of 5·7 days in children compared with 3·7 days in adults ( P = 0·03) …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the original reports of severe and fatal disease, prospective studies demonstrated seroconversion in asymptomatic or only mildly asymptomatic individuals [14,15]. Many risk factors for severe pH1N1 influenza were identified that are similar to the risk factors for severe seasonal influenza.…”
Section: Introductionmentioning
confidence: 88%